Overview [in Africa agriculture trade monitor 2021] - Bouët, Antoine; Tadesse, Getaw; Zaki, Chahir (AKADEMIYA2063, 2021)
This first chapter provides an overview of recent issues related to agricultural trade in Africa. Hence, the next section explains how the unprecedented shock of COVID-19 has had a major impact on trade and food security in Africa. The following section looks at the initial steps in the implementation of the African Continental Free Trade Area (AfCFTA) in 2021. The final section describes some issues concerning data and methodology used for this report